Silent corticotroph adenomas. - Karavitaki, N; Ansorge, O; Wass, J (2007)
Silent corticotroph pituitary adenomas (SCA) are defined as pituitary adenomas showing positive staining for adrenocorticotrophic hormone in immunohistochemical studies, but not associated with perioperative clinical or laboratory features of hypercortisolaemia. They account for 1.1-6% of surgically removed pituitary adenomas. Currently, two distinct pathologic subtypes of SCA are recognised. Their pathogenesis remains unclear. They present with local mass effects (headache, visual deterioration, cranial nerve palsies, endocrine dysfunction). The lack of manifestations of cortisol excess has not been conclusively explained. In surgical series, most tumours are macroadenomas with suprasellar extension present in 87-100% of the cases; this is in contrast to Cushing's disease, which is mostly attributed to microadenomas. Surgery remains the main therapeutic approach. Attempts to identify predictors of recurrence have not been successful. Management and follow-up protocols should be planned taking into account their potential aggressive behaviour, particularly upon recurrence. The development of florid pituitary Cushing's syndrome and local recurrence followed by metastatic disease (occasionally outside the central nervous system) have been rarely reported.